Controversy in use of mannitol in head injury - Wani, Abrar Ahad; Ramzan, Altaf U; Nizami, Furqan; Malik, Nayil K; Kirmani, A R; Bhatt, AR; Singh, Sarabjeet (Indian Journal of Neurotrauma, 2008)
The most commonly used drug in the patients of severe head injury is mannitol. The drug is classified pharmacologically as osmotic-diuretic but its mechanism of action in decreasing intracranial pressure is multi-factorial. Despite having dramatic results in the management of head injury patients the drug is still facing many controversies ranging from mechanism of action to the efficacy, especially is the light of evidence based medicine.
Keywords: head injury; mannitol